Internal determinants of profitability in Nepali commercial banks - Bohara, Indra Bahadur (Shanti Journal, 2024)
Bank is the financial institutions, which collects the deposit from the general public and institutions and provides loan to mobilize the resources in the economy that support to develop the stable economy in the country. The stable economy of the country depends on the successful operation and better financial performance of the banking industry. The stability and growth of the bank have direct relationship with its profitability. There are several internal and external determinants of measuring profitability of the bank. The main objective of this study is to examine the relationship between internal determinants and profitability (i.e. return on assets) and to analyze the impact of internal determinants on profitability position of Nepalese commercial banks.This study considered twenty commercial banks out of twenty-seven commercial banks operating in Nepal till fiscal year 2075/076. The sample size depends on the operation of 10 years in Nepalese banking industry. This study was based on the secondary data of commercial banks and collected data from the period of fiscal year 2071/072 to 2075/076 through their website. The study used the multiple regression analysis through SPSS software to measure the banks’ profitability in terms of Return on Asset (ROA) as a dependent variable and to analyze the impact of size of bank, employee efficiency, operating efficiency, management efficiency, interest cost and liquidity risk. The study found that the bank size, interest cost, management efficiency, liquidity risks and operational efficiency have negative relationship with ROA. On the other hand, employee efficiency has a positive and statistically significant relationship with banks’ profitability. However, the impact of operational efficiency and interest cost is statistically insignificant and other internal determinants are statistically significant against the banks’ profitability. The study suggests that the banking sectors should take into the consideration of the key internal factors in their operation to overcome their liquidity crisis and operational issues and to improve the profitability position of the commercial banks in Nepal. This study also opens the floor of the study in other banking financial institutions to analyze the determinants of profitability. The researchers can also study the external determinants of banks’ profitability in the future.